Anti-fouling and anti-graffiti coating and preparation method thereof
By using fluorine-containing acrylate copolymer, capsule microspheres and modified nanotitanium dioxide to construct the micro-nano rough interface, the problem of wear and hydrophilicity of the coating during the scrubbing process is solved, and the coating is efficient anti-fouling, graffiti and stability is achieved.
Patent Information
- Application Number
- CN202510104556.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-23
AI Technical Summary
During the repeated scrubbing and removal of contaminants or graffiti, the surface of the fluorine-containing acrylate coating will undergo severe wear, resulting in exposure of nanofillers, improving hydrophilicity, and affecting the anti-fouling and graffiti effect.
Fluoro-containing acrylate copolymer is used as the matrix, combined with capsule microspheres and modified nanotitanium dioxide to construct a micro-nano rough interface, improving the hydrophobic and oleophobic properties and use stability of the coating.
It significantly improves the anti-fouling and graffiti effect of the coating, and maintains good performance after multiple scrubbing and has good stability.
Smart Images

Figure CN119505622B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-fouling coatings, in particular to an anti-fouling and anti-graffiti coating and a preparation method thereof. Background Art
[0002] Anti-fouling and anti-graffiti coating is a coating with special surface functions. It has low surface energy, and is hydrophobic and oleophobic. Water-based or oily handwriting can be easily removed by wiping or washing. Surface dirt rolls off naturally, and it has self-cleaning properties. Fluorinated acrylate polymers have hydrophobic and oleophobic properties, chemical inertness, and thermal stability. Coatings prepared with fluorinated acrylate polymers as the matrix have good anti-fouling and anti-graffiti effects.
[0003] However, during the process of repeatedly washing and removing pollutants or graffiti, the surface of the fluorinated acrylate coating will be severely worn, causing the modified particles such as nanofillers in the coating to be directly exposed. The exposed positions of these nanoparticles lose the protection of the coating film, and their own hydrophilicity will be revealed, resulting in an increase in the overall hydrophilicity of the coating, affecting the anti-fouling and anti-graffiti effect of the coating. Based on this, an anti-fouling and anti-graffiti coating and a preparation method thereof are proposed. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides an anti-fouling and anti-graffiti coating and a preparation method thereof, which takes a fluorinated acrylate copolymer as a matrix, and constructs a micro-nano rough interface by combining capsule microspheres and modified nano titanium dioxide, thereby improving the hydrophobic and oleophobic properties and the stability of use of the coating.
[0005] To achieve the above object, the present invention provides the following technical solution: an anti-fouling and anti-graffiti coating, comprising the following raw materials in parts by weight: 70-80 parts of fluorine-containing acrylate copolymer, 10-15 parts of capsule microspheres, 12-15 parts of modified nano titanium dioxide, 0.1-0.3 parts of defoaming agent, 5-8 parts of curing agent, and 20-25 parts of solvent;
[0006] The capsule microspheres are composed of a fluorosilane core, a hollow mesoporous silica microsphere skeleton and a urea-formaldehyde resin shell from the inside to the outside.
[0007] Preferably, the preparation method of the fluorine-containing acrylate copolymer is as follows: S11, hexadecyl acrylate, hydroxypropyl methacrylate, part of dibenzoyl peroxide and part of xylene are placed in a reactor, and stirred for reaction at 90-95°C for 2-2.5 hours to obtain a reaction liquid; S12, perfluorooctylethyl methacrylate, remaining dibenzoyl peroxide and remaining xylene are added to the reaction liquid, and the reaction is continued at a temperature of 3-3.5 hours, and the temperature is reduced and the material is discharged to obtain a fluorine-containing acrylate copolymer.
[0008] Preferably, the mass ratio of hexadecyl acrylate, hydroxypropyl methacrylate and perfluorooctyl ethyl methacrylate is (8-10):(1-2):(2-3); the solid-liquid ratio of hexadecyl acrylate and xylene is 1:(2-3) g / mL; and the added amount of dibenzoyl peroxide is 1.5-2% of the total mass of hexadecyl acrylate, hydroxypropyl methacrylate and perfluorooctyl ethyl methacrylate.
[0009] Preferably, the preparation method of the capsule microspheres is as follows: S21, stirring and mixing urea and 37wt% formaldehyde solution, adjusting the pH to 8-9 with 10wt% sodium hydroxide solution, and reacting at 60-70°C for 1-1.2h to obtain urea-formaldehyde prepolymer; S22, ultrasonically dispersing hollow mesoporous silica microspheres, fluorosilane and toluene, and then adding sodium dodecylbenzene sulfonate to continue ultrasonic dispersion to obtain a suspension emulsion; S23, mixing the urea-formaldehyde prepolymer and the suspension emulsion, adjusting the pH to 3-4 with 10wt% hydrochloric acid solution, stirring and reacting at 60-65°C for 3-3.5h, and after the reaction is completed, centrifuging, washing, and drying to obtain capsule microspheres with fluorosilane as the core, hollow mesoporous silica microspheres as the skeleton, and urea-formaldehyde resin as the shell.
[0010] Preferably, in step S22, the fluorosilane is selected from dodecafluoroheptylpropyltrimethoxysilane and tridecafluorooctyltrimethoxysilane.
[0011] Preferably, in step S21, the mass ratio of urea to 37wt% formaldehyde solution is 1:3; in step S22, the mass ratio of hollow mesoporous silica microspheres, fluorosilane and toluene is 1:2:4;
[0012] In step S23, the mass ratio of the urea-formaldehyde prepolymer to the suspension emulsion is 7:3.
[0013] Preferably, the particle size of the capsule microspheres is 5-8 μm; the particle size of the modified nano-titanium dioxide is 50-100 nm.
[0014] Preferably, the modified nano titanium dioxide is obtained by surface-modifying nano titanium dioxide with a silane coupling agent.
[0015] Preferably, the defoamer is selected from silicone defoamers; the curing agent is selected from isophorone diisocyanate and hexamethylene diisocyanate; and the solvent is selected from xylene.
[0016] The present invention also provides a method for preparing an anti-fouling and anti-graffiti coating, comprising the following steps:
[0017] (1) uniformly stirring the fluorinated acrylate copolymer, capsule microspheres, modified nano titanium dioxide, defoaming agent and solvent to obtain a premix;
[0018] (2) Add a curing agent to the premix and stir evenly to obtain an anti-fouling and anti-graffiti coating.
[0019] The present invention provides an anti-fouling and anti-graffiti coating and a preparation method thereof, which has the following beneficial effects compared with the prior art:
[0020] The present invention uses a fluorinated acrylate copolymer as a matrix, and constructs a micro-nano rough interface by combining capsule microspheres of different particle sizes and modified nano titanium dioxide, thereby improving the hydrophobic and oleophobic properties of the coating, so that the coating performs well in terms of anti-fouling and anti-graffiti; and after being washed many times, the coating still has an excellent anti-fouling and anti-graffiti effect and has good stability.
[0021] The present invention prepares capsule microspheres with fluorosilane as the core, hollow mesoporous silica microspheres as the skeleton and urea-formaldehyde resin as the shell; after the coating is washed, the film wrapped on the surface of the capsule microspheres and the modified nano titanium dioxide is scraped off, and the hydrophilicity of the exposed position of the particles is relatively high, resulting in an increase in the overall hydrophilicity of the coating. At this time, the outer shell is worn and broken due to washing, and the fluorosilane inside it flows out through the mesopores and re-covers the exposed position of the capsule microspheres and the modified nano titanium dioxide, which is beneficial to reduce the overall hydrophilicity of the coating and enable it to continue to maintain a good hydrophobic and oleophobic effect; moreover, the hollow mesoporous silica microsphere skeleton has a good wear resistance function, which prevents the capsule microspheres from being severely worn after repeated washings and failing to construct a micro-nano rough interface, and also reduces the loss of fluorosilane inside it, thereby improving the use stability of the coating.
[0022] The present invention uses hexadecyl acrylate, hydroxypropyl methacrylate and perfluorooctyl ethyl methacrylate to prepare a copolymer that can form a crystalline state at room temperature. The fluorine element is more enriched on the coating surface, and the coating has obvious phase separation, which increases the roughness, thereby improving the hydrophobic and oleophobic properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0024] Figure 1 This is a schematic diagram of the structure of the capsule microsphere of the present invention;
[0025] Figure 2 This is the infrared spectrum of the fluorinated acrylate copolymer in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0027] Example 1
[0028] The preparation method of the fluorinated acrylate copolymer is as follows:
[0029] S11, adding hexadecyl acrylate, hydroxypropyl methacrylate, 40% of dibenzoyl peroxide (by mass) and 80% of xylene (by mass) into a reactor, stirring and reacting at 90° C. for 2.5 hours to obtain a reaction solution;
[0030] S12. Add perfluorooctylethyl methacrylate, the remaining 60% of dibenzoyl peroxide (by mass) and the remaining 20% of xylene (by mass) to the reaction solution, continue to keep the temperature for 3.5 hours, cool and discharge the material to obtain a fluorinated acrylate copolymer.
[0031] The mass ratio of the above-mentioned hexadecyl acrylate, hydroxypropyl methacrylate and perfluorooctyl ethyl methacrylate is 8:1:2; the solid-liquid ratio of hexadecyl acrylate and xylene is 1:2 g / mL; and the added amount of dibenzoyl peroxide is 1.5% of the total mass of hexadecyl acrylate, hydroxypropyl methacrylate and perfluorooctyl ethyl methacrylate.
[0032] Example 2
[0033] The preparation method of the fluorinated acrylate copolymer is as follows:
[0034] S11, putting hexadecyl acrylate, hydroxypropyl methacrylate, 50% of dibenzoyl peroxide (by mass) and 70% of xylene (by mass) into a reactor, stirring and reacting at 95° C. for 2 h to obtain a reaction solution;
[0035] S12. Add perfluorooctylethyl methacrylate, the remaining 50% of dibenzoyl peroxide (by mass) and the remaining 30% of xylene (by mass) to the reaction solution, continue to keep the temperature for 3 hours, cool and discharge the material to obtain a fluorinated acrylate copolymer.
[0036] The mass ratio of the above-mentioned hexadecyl acrylate, hydroxypropyl methacrylate and perfluorooctyl ethyl methacrylate is 10:2:3; the solid-liquid ratio of hexadecyl acrylate and xylene is 1:3 g / mL; and the added amount of dibenzoyl peroxide is 2% of the total mass of hexadecyl acrylate, hydroxypropyl methacrylate and perfluorooctyl ethyl methacrylate.
[0037] Example 3
[0038] The preparation method of capsule microspheres is as follows:
[0039] S21. Urea and 37 wt % formaldehyde solution are stirred and mixed at a mass ratio of 1:3, the pH is adjusted to 8 with 10 wt % sodium hydroxide solution, and the mixture is reacted at 70° C. for 1 h to obtain a urea-formaldehyde prepolymer.
[0040] S22. Ultrasonic dispersion of hollow mesoporous silica microspheres, fluorosilane (tridecafluorooctyltrimethoxysilane) and toluene, followed by addition of sodium dodecylbenzenesulfonate and continued ultrasonic dispersion to obtain a suspension emulsion; wherein the mass ratio of hollow mesoporous silica microspheres, fluorosilane (tridecafluorooctyltrimethoxysilane) and toluene is 1:2:4.
[0041] S23. Mix urea-formaldehyde prepolymer and suspension emulsion in a mass ratio of 7:3, adjust the pH to 3 with 10wt% hydrochloric acid solution, stir and react at 60°C for 3.5h, and after the reaction is completed, centrifuge, wash and dry to obtain capsule microspheres with fluorosilane (tridecafluorooctyltrimethoxysilane) as the core, hollow mesoporous silica microspheres as the skeleton and urea-formaldehyde resin as the shell.
[0042] In this embodiment, the particle size of the hollow mesoporous silica microspheres used is 3-5 μm, and the pore size is above 10 nm.
[0043] Example 4
[0044] The preparation method of capsule microspheres is as follows:
[0045] S21. Urea and 37 wt % formaldehyde solution were stirred and mixed at a mass ratio of 1:3, the pH was adjusted to 9 with 10 wt % sodium hydroxide solution, and the mixture was reacted at 60° C. for 1.2 h to obtain a urea-formaldehyde prepolymer.
[0046] S22. Ultrasonic dispersion of hollow mesoporous silica microspheres, fluorosilane (dodecylheptylpropyltrimethoxysilane) and toluene, followed by addition of sodium dodecylbenzenesulfonate and continued ultrasonic dispersion to obtain a suspension emulsion; wherein the mass ratio of hollow mesoporous silica microspheres, fluorosilane (dodecylheptylpropyltrimethoxysilane) and toluene is 1:2:4.
[0047] S23. Mix urea-formaldehyde prepolymer and suspension emulsion in a mass ratio of 7:3, adjust the pH to 4 with 10wt% hydrochloric acid solution, stir and react at 65°C for 3 hours, and after the reaction is completed, centrifuge, wash and dry to obtain capsule microspheres with fluorosilane (dodecylheptylpropyltrimethoxysilane) as the core, hollow mesoporous silica microspheres as the skeleton and urea-formaldehyde resin as the shell.
[0048] In this embodiment, the particle size of the hollow mesoporous silica microspheres used is 3-5 μm, and the pore size is above 10 nm.
[0049] Example 5
[0050] An anti-fouling and anti-graffiti coating comprises the following raw materials in parts by weight: 80 parts of fluorine-containing acrylate copolymer, 10 parts of capsule microspheres (particle size is 5-8 μm), 15 parts of modified nano titanium dioxide (particle size is 50-100 nm), 0.1 parts of BYK-085 defoamer, 8 parts of isophorone diisocyanate curing agent, and 20 parts of xylene solvent; wherein the modified nano titanium dioxide is prepared by surface-modifying nano titanium dioxide with a silane coupling agent KH-550.
[0051] The method for preparing the anti-fouling and anti-graffiti coating comprises the following steps:
[0052] (1) uniformly stirring the fluorinated acrylate copolymer, capsule microspheres, modified nano titanium dioxide, BYK-085 defoamer and xylene solvent to obtain a premix;
[0053] (2) Add isophorone diisocyanate curing agent to the premix and stir evenly to prepare an anti-fouling and anti-graffiti coating.
[0054] In this embodiment, the fluorine-containing acrylate copolymer in Example 1 and the capsule microspheres in Example 3 are used.
[0055] Example 6
[0056] An anti-fouling and anti-graffiti coating comprises the following raw materials in parts by weight: 75 parts of fluorine-containing acrylate copolymer, 12 parts of capsule microspheres (particle size is 5-8 μm), 15 parts of modified nano titanium dioxide (particle size is 50-100 nm), 0.2 parts of BYK-530 defoamer, 6 parts of hexamethylene diisocyanate curing agent, and 22 parts of xylene solvent; wherein the modified nano titanium dioxide is prepared by surface-modifying nano titanium dioxide with a silane coupling agent KH-560.
[0057] The method for preparing the anti-fouling and anti-graffiti coating comprises the following steps:
[0058] (1) uniformly stirring the fluorinated acrylate copolymer, capsule microspheres, modified nano titanium dioxide, BYK-530 defoaming agent and xylene solvent to obtain a premix;
[0059] (2) Add hexamethylene diisocyanate curing agent to the premix and stir evenly to prepare an anti-fouling and anti-graffiti coating.
[0060] In this embodiment, the fluorinated acrylate copolymer in Embodiment 1 and the capsule microspheres in Embodiment 4 are used.
[0061] Example 7
[0062] An anti-fouling and anti-graffiti coating comprises the following raw materials in parts by weight: 70 parts of fluorine-containing acrylate copolymer, 15 parts of capsule microspheres (particle size is 5-8 μm), 12 parts of modified nano titanium dioxide (particle size is 50-100 nm), 0.3 parts of BYK-077 defoamer, 5 parts of hexamethylene diisocyanate curing agent, and 25 parts of xylene solvent; wherein the modified nano titanium dioxide is prepared by surface-modifying nano titanium dioxide with a silane coupling agent KH-560.
[0063] The method for preparing the anti-fouling and anti-graffiti coating comprises the following steps:
[0064] (1) uniformly stirring the fluorinated acrylate copolymer, capsule microspheres, modified nano titanium dioxide, BYK-077 defoaming agent and xylene solvent to obtain a premix;
[0065] (2) Add hexamethylene diisocyanate curing agent to the premix and stir evenly to prepare an anti-fouling and anti-graffiti coating.
[0066] In this embodiment, the fluorinated acrylate copolymer in Embodiment 2 and the capsule microspheres in Embodiment 4 are used.
[0067] Comparative Example 1
[0068] An anti-fouling and anti-graffiti coating is basically the same as Example 6, except that the capsule microspheres are replaced by capsule microspheres A. The preparation method of capsule microspheres A is as follows:
[0069] S21. Urea and 37 wt % formaldehyde solution are stirred and mixed at a mass ratio of 1:3, the pH is adjusted to 8-9 with 10 wt % sodium hydroxide solution, and the mixture is reacted at 60-70° C. for 1-1.2 h to obtain a urea-formaldehyde prepolymer.
[0070] S22. Ultrasonic dispersion of fluorosilane (dodecylheptylpropyltrimethoxysilane) and toluene, followed by addition of sodium dodecylbenzenesulfonate and continued ultrasonic dispersion to obtain an emulsion; wherein the mass ratio of fluorosilane (dodecylheptylpropyltrimethoxysilane) to toluene is 1:2.
[0071] S23. Mix the urea-formaldehyde prepolymer and the emulsion in a mass ratio of 7:3, adjust the pH to 3-4 with a 10wt% hydrochloric acid solution, stir and react at 60-65°C for 3-3.5h, and after the reaction is completed, centrifuge, wash and dry to obtain capsule microspheres A with fluorosilane (dodecylheptylpropyltrimethoxysilane) as the core and urea-formaldehyde resin as the shell.
[0072] The method for preparing the anti-fouling and anti-graffiti coating comprises the following steps:
[0073] (1) uniformly stirring the fluorinated acrylate copolymer, capsule microsphere A, modified nano titanium dioxide, BYK-530 defoaming agent and xylene solvent to obtain a premix;
[0074] (2) Add hexamethylene diisocyanate curing agent to the premix and stir evenly to prepare an anti-fouling and anti-graffiti coating.
[0075] In this comparative example, the fluorine-containing acrylate copolymer in Example 1 was used.
[0076] Comparative Example 2
[0077] An anti-fouling and anti-graffiti coating comprises the following raw materials in parts by weight: 75 parts of fluorine-containing acrylate copolymer, 27 parts of capsule microspheres (with a particle size of 5-8 μm), 0.2 parts of BYK-530 defoamer, 6 parts of hexamethylene diisocyanate curing agent, and 22 parts of xylene solvent.
[0078] The method for preparing the anti-fouling and anti-graffiti coating comprises the following steps:
[0079] (1) uniformly stirring the fluorinated acrylate copolymer, capsule microspheres, BYK-530 defoamer and xylene solvent to obtain a premix;
[0080] (2) Add hexamethylene diisocyanate curing agent to the premix and stir evenly to prepare an anti-fouling and anti-graffiti coating.
[0081] In this comparative example, the fluorinated acrylate copolymer in Example 1 and the capsule microspheres in Example 4 were used.
[0082] Comparative Example 3
[0083] An anti-fouling and anti-graffiti coating comprises the following raw materials in parts by weight: 75 parts of a fluorine-containing acrylate copolymer, 27 parts of modified nano titanium dioxide (with a particle size of 50-100 nm), 0.2 parts of a BYK-530 defoamer, 6 parts of a hexamethylene diisocyanate curing agent, and 22 parts of a xylene solvent; wherein the modified nano titanium dioxide is obtained by surface-modifying the nano titanium dioxide with a silane coupling agent KH-560.
[0084] The method for preparing the anti-fouling and anti-graffiti coating comprises the following steps:
[0085] (1) uniformly stirring the fluorinated acrylate copolymer, modified nano titanium dioxide, BYK-530 defoamer and xylene solvent to obtain a premix;
[0086] (2) Add hexamethylene diisocyanate curing agent to the premix and stir evenly to prepare an anti-fouling and anti-graffiti coating.
[0087] In this comparative example, the fluorine-containing acrylate copolymer in Example 1 was used.
[0088] Comparative Example 4
[0089] An anti-fouling and anti-graffiti coating comprises the following raw materials in parts by weight: 75 parts of a fluorine-containing acrylate copolymer, 12 parts of capsule microspheres (with a particle size of 5-8 μm), 15 parts of modified barium sulfate (with a particle size of 5-8 μm), 0.2 parts of a BYK-530 defoamer, 6 parts of a hexamethylene diisocyanate curing agent, and 22 parts of a xylene solvent; wherein the modified barium sulfate is obtained by surface-modifying barium sulfate with a silane coupling agent KH-560.
[0090] The method for preparing the anti-fouling and anti-graffiti coating comprises the following steps:
[0091] (1) uniformly stirring the fluorinated acrylate copolymer, capsule microspheres, modified barium sulfate, BYK-530 defoaming agent and xylene solvent to obtain a premix;
[0092] (2) Add hexamethylene diisocyanate curing agent to the premix and stir evenly to prepare an anti-fouling and anti-graffiti coating.
[0093] In this comparative example, the fluorinated acrylate copolymer in Example 1 and the capsule microspheres in Example 4 were used.
[0094] Comparative Example 5
[0095] An anti-fouling and anti-graffiti coating is basically the same as Example 6, except that the fluorinated acrylate copolymer is replaced by fluorinated acrylate copolymer A.
[0096] The preparation of the fluorinated acrylate copolymer A is basically the same as that of the fluorinated acrylate copolymer in Example 1, except that hexadecyl acrylate is replaced by lauryl acrylate.
[0097] The method for preparing the anti-fouling and anti-graffiti coating comprises the following steps:
[0098] (1) uniformly stirring the fluorinated acrylate copolymer A, capsule microspheres, modified nano titanium dioxide, BYK-530 defoaming agent and xylene solvent to obtain a premix;
[0099] (2) Add hexamethylene diisocyanate curing agent to the premix and stir evenly to prepare an anti-fouling and anti-graffiti coating.
[0100] In this comparative example, the capsule microspheres in Example 4 were used.
[0101] Quality Inspection
[0102] 1. The anti-fouling and anti-graffiti coatings in Examples 5-7 and Comparative Examples 1-5 were brushed onto PET plastic plates and cured to obtain coating samples. The coating samples were tested in accordance with the standard of JG / T 304-2011. The specific results are shown in the following table.
[0103] Table 1 Antifouling performance
[0104]
[0105] From the above table, we can see that:
[0106] (1) The coating samples in Examples 5-7 have excellent performance in terms of anti-fouling and anti-graffiti.
[0107] (2) Compared with Example 6, the coating samples in Comparative Examples 2-4 all had poor anti-fouling and anti-graffiti properties due to the inability to construct a micro-nano rough interface.
[0108] (3) Compared with Example 6, the matrix used in Comparative Example 5 is fluorinated acrylate copolymer A, which uses lauryl acrylate with a relatively short alkane chain length. The copolymer formed at room temperature is not crystalline, which ultimately affects the hydrophobic and oleophobic effect of the coating.
[0109] 2. The anti-fouling and anti-graffiti coatings in Examples 5-7 and Comparative Example 1 were brushed onto a PET plastic plate and cured to obtain a coating sample. After washing 500 times, the sample was left to stand for 12 hours and then subjected to a water contact angle test. The stability of the coating sample was characterized by the change rate of the water contact angle of the coating before and after washing. The change rate calculation formula is as follows:
[0110] ;
[0111] In the above formula: It represents the water contact angle of the coating sample before washing; It represents the water contact angle of the coating sample after washing.
[0112] The specific results are shown in the following table.
[0113] Table 2 Stability
[0114]
[0115] From the above table, we can see that:
[0116] (1) Compared with Example 6, the water contact angle of the coating sample in Comparative Example 1 decreased significantly after washing, indicating that in the absence of hollow mesoporous silica microspheres as a skeleton, capsule microspheres A are easily worn, resulting in damage to the micro-nano rough interface constructed between capsule microspheres and modified nano-titanium dioxide, thereby affecting the quality of the coating; on the other hand, the capsule microspheres in Example 6 use hollow mesoporous silica microspheres as a skeleton, and the constructed micro-nano rough interface is more wear-resistant and wash-resistant, and can also protect the fluorosilane therein, reducing the loss during washing, and performing better in terms of stability.
[0117] (2) Compared with Example 6, the water contact angle of the coating sample in Comparative Example 3 decreased significantly after washing. This is because after washing, the modified nano-titanium dioxide was partially exposed, and the silane coupling agent film and copolymer film wrapped in the exposed part were damaged. The hydrophilicity of the exposed part increased, resulting in a decrease in the overall hydrophobicity of the coating.
[0118] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An anti-fouling and anti-graffiti coating, characterized in that: The invention comprises the following raw materials in parts by weight: 70-80 parts of fluorine-containing acrylate copolymer, 10-15 parts of capsule microspheres, 12-15 parts of modified nano titanium dioxide, 0.1-0.3 parts of defoaming agent, 5-8 parts of curing agent and 20-25 parts of solvent; The capsule microspheres are composed of a fluorosilane core, a hollow mesoporous silica microsphere skeleton and a urea-formaldehyde resin shell from the inside to the outside; The preparation method of the fluorinated acrylate copolymer is as follows: S11, adding hexadecyl acrylate, hydroxypropyl methacrylate, part of dibenzoyl peroxide and part of xylene into a reactor, stirring and reacting at 90-95° C. for 2-2.5 hours to obtain a reaction solution; S12, add perfluorooctylethyl methacrylate, remaining dibenzoyl peroxide and remaining xylene to the reaction solution, continue to keep the temperature for 3-3.5 hours, cool and discharge the material to obtain a fluorine-containing acrylate copolymer.
2. The anti-fouling and anti-graffiti coating according to claim 1, characterized in that: In steps S11-S12, the mass ratio of hexadecyl acrylate, hydroxypropyl methacrylate and perfluorooctylethyl methacrylate is (8-10): (1-2): (2-3); The solid-liquid ratio of hexadecyl acrylate to xylene is 1:(2-3) g / mL; The added amount of the dibenzoyl peroxide is 1.5-2% of the total mass of hexadecyl acrylate, hydroxypropyl methacrylate and perfluorooctylethyl methacrylate.
3. The anti-fouling and anti-graffiti coating according to claim 1, characterized in that: The preparation method of the capsule microspheres is as follows: S21, stirring and mixing urea and 37 wt % formaldehyde solution, adjusting the pH to 8-9 with 10 wt % sodium hydroxide solution, and reacting at 60-70° C. for 1-1.2 h to obtain a urea-formaldehyde prepolymer; S22, ultrasonically dispersing the hollow mesoporous silica microspheres, fluorosilane and toluene, and then adding sodium dodecylbenzene sulfonate and continuing ultrasonic dispersion to obtain a suspension emulsion; S23, mixing the urea-formaldehyde prepolymer and the suspension emulsion, adjusting the pH to 3-4 with 10wt% hydrochloric acid solution, stirring and reacting at 60-65°C for 3-3.5h, and after the reaction is completed, centrifuging, washing and drying to obtain capsule microspheres with fluorosilane as the core, hollow mesoporous silica microspheres as the skeleton and urea-formaldehyde resin as the shell.
4. The anti-fouling and anti-graffiti coating according to claim 3, characterized in that: In step S22, the fluorosilane is selected from dodecafluoroheptylpropyltrimethoxysilane and tridecafluorooctyltrimethoxysilane.
5. The anti-fouling and anti-graffiti coating according to claim 3, characterized in that: In step S21, the mass ratio of urea to 37wt% formaldehyde solution is 1:3; In step S22, the mass ratio of the hollow mesoporous silica microspheres, fluorosilane and toluene is 1:2:4; In step S23, the mass ratio of the urea-formaldehyde prepolymer to the suspension emulsion is 7:
3.
6. The anti-fouling and anti-graffiti coating according to claim 1, characterized in that: The particle size of the capsule microsphere is 5-8 μm; the particle size of the modified nano titanium dioxide is 50-100 nm.
7. The anti-fouling and anti-graffiti coating according to claim 1, characterized in that: The modified nano titanium dioxide is prepared by surface-modifying the nano titanium dioxide with a silane coupling agent.
8. The anti-fouling and anti-graffiti coating according to claim 1, characterized in that: The defoamer is selected from silicone defoamers; the curing agent is selected from isophorone diisocyanate and hexamethylene diisocyanate; and the solvent is selected from xylene.
9. The method for preparing the anti-fouling and anti-graffiti coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) uniformly stirring the fluorinated acrylate copolymer, capsule microspheres, modified nano titanium dioxide, defoaming agent and solvent to obtain a premix; (2) Add a curing agent to the premix and stir evenly to obtain an anti-fouling and anti-graffiti coating.
Citation Information
Patent Citations
Autocrine low-surface-energy flow-resistance-reducing paint
CN102134425A
Fluorine-containing acrylate copolymer cationic emulsion as well as preparation method and application thereof
CN102492087A
Cited By
Preparation method of UV-cured long-chain organic silicon modified polyurea as well as product and application of UV-cured long-chain organic silicon modified polyurea
CN122381296A